2006
DOI: 10.1111/j.1540-4560.2006.00469.x
|View full text |Cite
|
Sign up to set email alerts
|

Extended Contact through Story Reading in School: Reducing Children's Prejudice toward the Disabled

Abstract: The aim of this study was to develop and assess a prejudice-reduction intervention for young children based on a relatively recent psychological concept, extended contact. A number of extended contact interventions were tested based on different models of generalized intergroup contact. A 3 (type of extended contact: neutral, decategorization, and "intergroup") × 2 (time of interview: pre-vs. post-extended contacts) mixed design was used, with the latter variable being within participants. Non-disabled childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
220
1
11

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 261 publications
(238 citation statements)
references
References 53 publications
6
220
1
11
Order By: Relevance
“…Extended contact has also revealed positive outcomes in improving attitudes of TD children towards peers with disabilities. Cameron and Rutland (2006) showed that 5-10 year old children who read stories portraying TD children befriending children with disabilities showed more positive attitudes and behavioural intentions towards those peers compared to control participants. In other words, extended contact may improve attitudes by knowing that "my friend's friend is my friend" (Dovidio et al, 2011, p. 150).…”
Section: Intergroup Contactmentioning
confidence: 97%
“…Extended contact has also revealed positive outcomes in improving attitudes of TD children towards peers with disabilities. Cameron and Rutland (2006) showed that 5-10 year old children who read stories portraying TD children befriending children with disabilities showed more positive attitudes and behavioural intentions towards those peers compared to control participants. In other words, extended contact may improve attitudes by knowing that "my friend's friend is my friend" (Dovidio et al, 2011, p. 150).…”
Section: Intergroup Contactmentioning
confidence: 97%
“…While homophobic bullying has been explained using numerous theories such as scapegoating, social identity theory, deindividuation theory, social ranking theory, and status construction theory (Rivers, 2011), the participants' belief that transactions with LGBTQ literature could lead to a reduction in homophobia and bullying align with intergroup contact theory (Allport, 1954) and specifically with an extended contact effect (Wright, Aron, McLaughlin-Volpe, & Ropp, 1997). While the extended contact effect has been investigated using children's literature to reduce negative attitudes toward the disabled (Cameron & Rutland, 2006), there are no known studies to this author that specifically measure whether instruction of LGBTQ themed literature decreases homophobia in students or reduces the frequency of bullying. This is an area ripe for future research and scholars should investigate the possible effects that instruction of LGBTQ themed texts could have on homophobia and/or bullying.…”
Section: Discussionmentioning
confidence: 99%
“…Elde edilen sonuçlar ZY bireylerle NGG akranlarının doğrudan etkileşimde bulunmalarının ZY bireylerin sosyal kabul düzeyini arttırdığı yönündeki farklı araştırmalara ait bulgularla paralellik göstermektedir (Uçar 2008;Khare, 2006;Aktaş ve Küçüker, 2002). Bu araştırmanın sonuçları yetersizliği olan bireylere yönelik etkileşim projesi içinde yer alanların (Melekoğlu,20 3), yetersizliği olan bireylerle düzenli olarak bir arada olma çalışma deneyimi olanların (Yazbeck, McVilly, Parmenter, 2004), yetersizliği olan bireylerle aktif etkileşim içinde olanların (Meyer,Gouiver,Duke & Advokat,200 ,s.5 ), yetersizliği olan bireyler hakkında bilgisi olan ve bu bireylerle çalışma deneyimi olanların (Avramidis, Bayliss & Burden, 2000) ve özel gereksinimli bireylerle ilişki kurmaya dayalı programlara katılan ilkokul öğrencilerinin (Cameron & Rutland, 2006) yetersizliği olan bireylere yönelik tutumlarının daha olumlu olduğunu ortaya koyan farklı araştırma sonuçlarıyla benzerlik göstermektedir.…”
Section: Tartişma Sonuç Ve öNeri̇lerunclassified